The Role of Religiosity, Consumer Animosity, and Ethnocentrism in Explaining the Boycott Motivation - Lestari, Puji; Jazil, Thuba (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The protracted conflict between Israel and the Palestinian Hamas group, culminating with an Israeli offensive in October 2023, has caused significant suffering to the Palestinian people. The response to the attack, including international support and a fatwa from the Indonesian Ulema Council (MUI), has prompted Indonesians to boycott products linked to Israel. This study aims to investigate the effect of religiosity, animosity and ethnocentrism on the motivation for boycotting Unilever Indonesia products related to the company's commitment to Israel, focusing on these factors. This type of research is quantitative descriptive with the SEM-PLS approach. The application used is SmartPLS version 4.0.0 with sample data used by 162 respondents through the distribution of questionnaires. The results show that the variables religiosity, consumer animosity and ethnocentrism have a positive and significant influence on the motivation to boycott Unilever Indonesia products. These findings highlight the importance of paying attention to psychological and social factors in the analysis of consumer behavior and their impact on companies and society at large. It also suggests that companies must take into account the social and political implications of their policies, as well as understand the values and beliefs underlying consumers' motivations for boycotting.